Formation of Innovative Business Models of Enterprises of the Tourism Industry in the Context of a Systemic Crisis - Evgeniy Fedorovich Cheberko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The paper discusses the causes of the acute crisis situation in the tourist industry. Named the main reasons of its occurrence. The main directions of overcoming the crisis, at both the macro and micro levels. The focus is on forming the innovative business models of enter-prises of the tourism industry.